PENGARUH KONSENTRASI CUKA KAYU DAN MEDIA TANAM PADA PERTUMBUHAN SETEK PUCUK PANGAL (Baccaurea bracteata Muell) - Maryam, .; Ekamawanti, Hanna Artuti; Manurung, Togar Fernando (Universitas Tanjungpura, 2019)
Pangal is one of the peat forest plant species that can be used to restore degraded peat forest. The purpose of this study was to obtain the most suitable concentration of wood vinegar for the growth of pangal bud cuttings planted in cocopeat or cocopeat growing media + hust charcoal. This study uses the experimental split plot method with a complete randomized pattern (CRD). Treatment factor as the main plot of media with 2 levels of (cocopeat and cocopeat + husk charcoal 2:1) and subplot with concentration Wood vinegar 3 levels (3%, 3.5% and 4%) with 5 replications. The results showed that the percentage of live of cuttings and the highest rooted percentage was in a combination of treatment with media and 4% wood vinegar concentration with a percentage of live of the cut reaching 100%. Significant treatment increases the length of primary roots and the number of roots found in the growth of thr primary root length is (4.19 cm) in the treatment of cocopeat media and the concentration of 3% wood vinegar can increase the growth of the primary roots length, for the highest average number of primary roots which is 6.40 also in the same treatment the same is cocopeat media with a dose of 3% wood vinegar. Significant treatment increases thenumber of roots is found in the treatment of secondary root with an average value 33.6 was in the of cocopeat media treatment with 4% wood vinegar dose, while the highest number of leaves with an average 6.60 was in the treatment of cocopeat + husk charcoal with 4% wood vinegar concentration. Wood vinegar concentration and the planting média that are most suitable for shoots cuttings are the concentration of wood vinegar 3% and 4% which can be applied to cocopeat media either without or with the addition of husk charcoal.Keywords: Baccaurea bracteata Muell, growth media, shoot cutting, wood vinegar